2003
DOI: 10.1254/jphs.93.451
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Repetitive Transcranial Magnetic Stimulation on Extracellular Serotonin Concentration in the Rat Prefrontal Cortex

Abstract: Abstract. Repetitive transcranial magnetic stimulation (rTMS) changes the function of the cortex. This study clarified the effects of acute rTMS treatment on extracellular serotonin (5-HT) concentrations in the rat prefrontal cortex (PFC) by using in vivo microdialysis methods. Each rat received acute rTMS treatment of the frontal brain at 500 stimuli from twenty trains applied at 25 Hz for 1 s at 1-min intervals between trains. Sham-treated rats received the same handling procedure and sound of the stimulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Previous studies have demonstrated an increase in the responsiveness of the serotonergic system over repeated social interactions (Beitia et al, 2005; Devoino et al, 2003; Filipenko et al, 2002). The stress of being handled and anesthetized in the first experiment could also have contributed to the effect of experience (Levine 1959; Kanno et al 2003). Although the change we observed was relatively small, it raises the possibility that the mice experienced other events prior to our study that could have contributed to inter-individual differences in the responsiveness of their serotonergic systems to social intrusion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated an increase in the responsiveness of the serotonergic system over repeated social interactions (Beitia et al, 2005; Devoino et al, 2003; Filipenko et al, 2002). The stress of being handled and anesthetized in the first experiment could also have contributed to the effect of experience (Levine 1959; Kanno et al 2003). Although the change we observed was relatively small, it raises the possibility that the mice experienced other events prior to our study that could have contributed to inter-individual differences in the responsiveness of their serotonergic systems to social intrusion.…”
Section: Discussionmentioning
confidence: 99%
“…These electrical and transcranial magnetic stimulations have several similar effects on neuronal processes as: modulation of nonlinear ion currents, neuronal membrane potentials, neuronal metabolic (oxidative) processes, neurotransmitters release, etc. (Caramia et al, 1991;Rosenthal and Sick, 1992;You et al, 1998;Juckel et al, 1999;Oliviero et al, 1999;Walsh and Cowey, 2000;Strafella et al, 2001;Kanno et al, 2003;Jelenković et al, 2006).…”
Section: Phosphenes As Electrically or Magnetically Induced Bioluminementioning
confidence: 99%
“…Associated with this treatment have been reports of changes in several neurotransmitters and neuroactive agents, including dopamine,1925 catecholamines and other biogenic amines,2630 serotonin,31,32 gamma-aminobutyric acid (GABA),3335 hormones,3638 other chemical moieties,3948 and interactions among these moieties2729,40,46 in the brain, blood plasma, and saliva.…”
mentioning
confidence: 99%